DOMINASI BAHASA ARAB DAN EFEK BAHASA GLOBAL PADA LANSKAP PEMASARAN PRODUK MUSLIM - Budiman, Arif; Khristianto, Khristianto (Sunan Kalijaga State Islamic University Yogyakarta, 2025)
Yogyakarta, a city with a significant Muslim population, has seen a rise in Muslim product stores that cater to both local and global consumer demands. These stores use diverse linguistic resources to appeal to a broad customer base, reflecting the influence of both local cultural values and global commercial trends. The study investigates how language is employed in naming these stores. This research was conducted to 1) describe the language use in the names of Muslim-product stores, 2) explain the language-use pattern of the store names, and 3) identify the unique syntax of store names. This study adopted a qualitative-descriptive approach, with a survey method. Data was collected by observing Muslim product shops in the city of Yogyakarta and recording shopfronts/façade shop data by recording it with a digital camera on a cellphone. Besides, the data collection was also carried out through digital surveys via Google Map. This was carried out to complement the results of conventional survey and also as a data verification step. In particular, this research will specifically focus on the textual data of shop names. The data will be analyzed interactively to categorize based on the linguistic form, constituent elements and syntactic patterns of the names. Based on the analysis results, it can be concluded 1) four languages are used in the shop name: Indonesian, English, Arabic, Javanese. They are used in mono-, bi-, and multilingual signs, with a predominance of multilingualism, 2) the naming of the stores shows the elements of name, product, quality, and target consumer; generally the name identity is chosen in Arabic, and the product is in English, and 3) structurally, Indonesian shop name phrases employ English rule, giving a deviating pattern, which implies a strong influence of the global language.